Degrees of English language acquisition and its relationship to grammar proficiency of INHS fourth year students - Torreces, Ramir C.
This exploratory study was undertaken to determine the degree of acquisition of English language of the fourth year students in INHS, and to relate this grammar proficiency. It also sought to determine the difference in the degree of acquisition to: (a) sex; (b) curricular program; (c) family monthly income; and (d) dialect spoken at home., The Acquisition of the English Language Questionnaire (AELQ), a five-part researcher-constructed self-assessment questionnaire was used to ascertain students' degree of acquisition and Grammar Proficiency Test (GPT), a 70-item grammar test, was used to assess their level of grammar proficiency. Both instruments were validated by experts and pilot tested. Using stratified random sampling, a total of 170 subjects was identified from the five curricular programs. The questionnaires were administered and responses were organized. Descriptive statistics were used to analyze the data. The findings revealed that, in general, fourth year students achieved an integration degree of exposure to the English language. This indicates that fourth year students used English (in speaking and writing), watched, read, and listened to materials presented in English when necessary or when they felt like engaging into it, and had positive attitudes toward the English language. However, there was a significant difference in their degree of acquisition of the English language only when grouped according to curricular program. In the grammar proficiency test, students registered a proficient level - most of them knew the basic rules of grammar. When grouped according to curricular program, there was a significant difference among the scores. EOC had the lowest proficiency scores (less proficient) and SSC had the highest, though it shared a proficient level together with RC, SPA, and SOF. The pearson r correlation coefficient revealed that there was a low positive relationship between the students' assessment of their degree of acquisition of the English language and their level of grammar proficiency. Thus, the higher the degree of acquisition of the English language, the higher the grammar proficiency scores of the student. These results suggest that the degree of acquisition of the English language influences the level of grammar proficiency of learners, supporting Schumann's Acculturation Theory. It is also consistent with the findings of some researchers such as Stauble, and Graham & Brown.